Efektivitas Video Pendek sebagai Media Pemasaran Digital: Bukti Empiris dari Konsumen Milenial dan Gen Z - Airyq, Irnin Miladdyan; Putri, Intan Meilani; Sundoro, Fredericho Mego; Aswin, Aswin (Journal of Economic and Business Retail, 2025)
This study aims to analyze the influence of short videos on the actual purchasing behavior of young consumers in Semarang City. Using a quantitative approach, data were collected through questionnaires from 100 respondents exposed to a short video of the fictional product "Aroma Plus." Results from multiple linear regression analysis revealed that product information (? = 0.394), perceived value (? = 0.306), celebrity influence (? = 0.261), and video content (? = 0.178) significantly affected purchasing behavior. These findings highlight that short videos are not only effective in capturing attention but also in driving actual purchases, particularly when combining functional information and emotional value. The study offers practical implications for businesses in designing more effective short video-based marketing strategies.